Compound semiconductor composition, thin film, solar cell, thermoelectric material using the same, and manufacturing method thereof

JP7636036B2Active Publication Date: 2025-02-26NAT INST FOR MATERIALS SCI
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023534761
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-12
Filing Date
2022-07-07
Publication Date
2025-02-26
Estimated Expiration
2042-07-07

AI Technical Summary

Benefits of technology

【0027】 本発明によれば、Sn原子とS原子からなり、直方晶系の結晶構造を有するSnS化合物と、前記SnS化合物にドープされている1種又は2種以上の原子と、を含み、前記のドープされている原子の少なくとも1種が、Sn2+のイオン半径よりも大きなイオン半径を有する2価の陽イオンとなる原子である、化合物半導体組成物を提供することができるので、既存のSnS系化合物半導体組成物とは異なる新規のSnS系化合物半導体組成物が提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007636036000001
    Figure 0007636036000001
  • Figure 0007636036000002
    Figure 0007636036000002
  • Figure 0007636036000003
    Figure 0007636036000003
Patent Text Reader

Abstract

The present invention addresses the problem of providing a new SnS-type compound semiconductor composition comprising: an SnS compound containing two species of atoms, namely, Sn atoms and S atoms; and one or more species of atoms doped into the SnS compound. The present invention provides a compound semiconductor composition that includes: an SnS compound comprising Sn atoms and S atoms and having a orthorhombic crystal structure; and one or more species of atoms doped into the SnS compound. The one or more species of atoms doped into the SnS compound are bivalent positive ion atoms having an ionic radius larger than the ionic radius of Sn2+.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a compound semiconductor composition, and more specifically, to a compound semiconductor composition comprising an SnS compound consisting of Sn atoms and S atoms and having an orthorhombic crystal structure, and one or more types of atoms doped into the SnS compound. The present invention also relates to a thin film (particularly, a thin film solar cell) using the above-mentioned compound semiconductor composition and a manufacturing method thereof, and a multi-junction solar cell (particularly, a top cell or a middle cell constituting a multi-junction solar cell) using the above-mentioned compound semiconductor composition. The present invention also relates to a powder compact of the above-mentioned compound semiconductor composition, a thermoelectric material using the same, and a method for producing the powder compact. [Background technology]

[0002] Semiconductors generally refer to individual elements such as transistors and diodes (i.e., discrete semiconductor components) or ICs (i.e., integrated circuits) that integrate circuits composed of transistors, etc., and are indispensable in our daily lives.

[0003] For example, solar cells, which utilize solar energy, are expected to be a promising renewable energy technology that is clean for the global environment and helps prevent global warming. However, these solar cells also typically use semiconductors as the material used to convert light into electricity. Semiconductors are also used in thermoelectric materials, which are used to convert heat into electricity. Semiconductor materials used in solar cells include silicon-based semiconductor compositions, compound semiconductor compositions, and organic semiconductor compositions.

[0004] Silicon-based semiconductor compositions use readily available silicon and can be used to create solar cells with high conversion efficiency. However, due to factors such as high manufacturing costs and the need to alleviate silicon shortages caused by the rapid expansion of demand for solar cells, there is a demand for the development of solar cells that use new semiconductors that do not use silicon.

[0005] Compound semiconductor compositions have excellent properties such as excellent high-speed signal processing because the electron transfer speed is much faster than that of silicon, operation at low voltage, reaction to light, and microwave emission. In addition, as a solar cell, compound semiconductor compositions have excellent properties such as excellent radiation resistance and heat resistance compared to silicon, and it is said that it is possible to make a solar cell with high conversion efficiency. In addition, since compound semiconductor compositions combine two or more elements (specifically, two or more types of atoms), it is possible to prepare many types of semiconductors by changing the combination, and it is applicable to a wide range of applications and is highly versatile. Therefore, compound semiconductor compositions have attracted particular attention as semiconductor compositions that can replace silicon-based semiconductor compositions, and research and development of them is being actively conducted.

[0006] Representative examples of compound semiconductor compositions include compounds of Group III and Group V of the periodic table (e.g., GaAs, InP) and compounds of Group II and Group VI (e.g., CdTe, ZnSe). Representative examples of compound semiconductor compositions used as solar cells include CIS semiconductor compositions made from copper (Cu), indium (In), and selenium (Se), CIGS semiconductor compositions made from copper (Cu), indium (In), selenium (Se), and gallium (Ga), CdTe semiconductor compositions made from cadmium (Cd) and tellurium (Te), and GaAs semiconductor compositions made from gallium (Ga) and arsenic (As). However, these typical compound semiconductor compositions have the problem that they contain rare atoms known as rare metals, such as In, Te, and Se, and toxic atoms, such as As and Cd.

[0007] On the other hand, the constituent elements of the SnS compound semiconductor composition are two atoms, Sn and S, both of which are inexpensive and have a low environmental impact. For example, Patent Document 1 discloses a method for producing a semiconductor sintered film that does not use toxic atoms, since the Cd atom used in the production of a CdS / CdTe-based compound semiconductor solar cell sintered film is a toxic atom. The method includes adding tin halide to tin(II) sulfide powder as a flux for promoting the sintering reaction to produce a SnS semiconductor sintered film. In addition, a SnS-based compound semiconductor composition in which other atoms are added (specifically, doped) to a SnS compound consisting of two atoms, Sn and S, has also been reported (see Patent Document 2, Non-Patent Documents 1 and 2).

[0008] In this application, in order to distinguish between an SnS compound consisting of two atoms, Sn and S, and a compound obtained by adding (specifically, doping) another element to this SnS compound, the former will be referred to as an "SnS compound" and the latter as an "SnS-based compound" for convenience. Therefore, in this application, an "SnS compound semiconductor composition" means a semiconductor composition of an SnS compound consisting of two atoms, Sn and S, and an "SnS-based compound semiconductor composition" means a semiconductor composition of a compound obtained by adding another element to the SnS compound. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Application Publication No. 06-321538 [Patent Document 2] Patent Publication No. 2019-178012 [Non-patent literature]

[0010] [Non-Patent Document 1] Julien Vidal et al., “Structural and electronic modification of photovoltaic SnS by alloying”, Applied Physics., 115, page 113507(2014) [Non-Patent Document 2] Tohoku University Press Release, Success in growing large tin sulfide single crystals!, August 21, 2020 Summary of the Invention [Problem to be solved by the invention]

[0011] The SnS compound semiconductor composition is a p-type semiconductor composition. For example, since a solar cell is basically constructed by heterojunction of a p-type compound semiconductor composition and an n-type compound semiconductor composition, a solar cell using a p-type SnS compound semiconductor composition is constructed by heterojunction of this SnS compound semiconductor composition with, for example, an n-type CdS compound semiconductor composition consisting of two atoms, Cd and S. However, solar cells constructed by forming a heterojunction between a p-type SnS compound semiconductor composition and an n-type CdS compound semiconductor composition cannot be expected to have high conversion efficiency because the interface between the CdS compound and the SnS compound has a large band offset.

[0012] Therefore, in order to eliminate such a band offset (specifically, to theoretically make the band offset 0 eV), attempts have been made to solve the above-mentioned problems by synthesizing an n-type SnS-based compound semiconductor composition and forming a homojunction with a p-type SnS compound semiconductor composition (see Patent Document 2 and Non-Patent Document 2). However, in the method of Patent Document 2 in which an n-type SnS-based compound semiconductor composition is synthesized by adding bromine to an SnS compound, the n-type SnS-based compound semiconductor composition obtained is merely a powder. In addition, in the method of Non-Patent Document 2 in which a single crystal of an n-type SnS-based compound semiconductor composition is synthesized by adding chlorine or bromine to an SnS compound, although a single crystal larger than the conventional one is obtained, it is not large enough to be put into practical use as a thin film device requiring a large area thin film. Thus, there is a problem that the existing n-type SnS-based compound semiconductor compositions have not yet been put into practical use as a thin film device or the like. Therefore, there is a demand for the development of a new n-type SnS-based compound semiconductor composition that differs from the existing SnS-based compound semiconductor compositions.

[0013] Additionally, as a means of increasing the efficiency of solar cells to exceed 40% conversion efficiency, there has been active development of multi-junction (tandem) solar cells, which combine cells with different properties. However, when designing a multi-junction solar cell by combining an SnS compound semiconductor composition with a solar cell that uses a widely used single crystal of silicon as a semiconductor composition (so-called "single crystal silicon solar cell"), the band gap of the SnS compound is small, about 1.3 to 1.4 eV, which is close to the band gap of silicon (1.1 eV), so there is no advantage to using the SnS compound semiconductor composition in combination with a single crystal silicon solar cell in a multi-junction solar cell. In other words, there is an inherent problem that it is difficult to use the SnS compound semiconductor composition in such a multi-junction solar cell.

[0014] In addition, there is currently a demand for solar cells and thermoelectric materials that can provide superior physical properties (for example, conversion efficiency) to those of existing solar cells and thermoelectric materials, by utilizing SnS-based compound semiconductor compositions that are inexpensive and have a low environmental impact.

[0015] In order to solve the above problems, the present invention aims to provide a novel SnS-based compound semiconductor composition comprising an SnS compound consisting of two atoms, Sn and S, and one or more types of atoms doped into the SnS compound.

[0016] For example, the object is to provide a SnS-based compound semiconductor composition having a band gap larger than 1.5 eV, which is the band gap of the SnS compound, as the above-mentioned novel SnS-based compound semiconductor composition. Furthermore, the object is to provide a novel SnS-based compound semiconductor composition that can operate as a solar cell (specifically, one that has a conversion efficiency (%) of a certain amount (more than 0%)) even when the novel SnS-based compound semiconductor composition having a band gap larger than 1.5 eV, which is the band gap of the SnS compound, is heterojunctioned with an n-type CdS compound semiconductor composition. The provision of such a solar cell is an indicator that the novel SnS-based compound semiconductor composition having a band gap larger than 1.5 eV, which is the band gap of the SnS compound, is useful in designing a solar cell having the above-mentioned conversion efficiency of more than 40%.

[0017] Alternatively, an object of the present invention is to provide a p-type SnS-based compound semiconductor composition that can reduce the band offset at the interface between CdS and SnS (in other words, can be easily made n-type) even when it is heterojunctioned with an n-type CdS compound semiconductor composition as the above-mentioned novel SnS-based compound semiconductor composition. As is clear from the description of the present specification, the above-mentioned "it becomes easier to change to n-type" means that it becomes easier to change to n-type when the band gap of the SnS-based compound semiconductor composition becomes larger.

[0018] Alternatively, an object of the present invention is to provide, as the above-mentioned novel SnS-based compound semiconductor composition, a novel n-type SnS-based compound semiconductor composition capable of forming a homojunction, which differs from existing n-type SnS-based compound semiconductor compositions.

[0019] Alternatively, an object of the present invention is to provide a thin film, a thin film solar cell, a top cell for a multijunction solar cell, a middle cell for a multijunction solar cell, or a multijunction solar cell, which contains the above-mentioned novel SnS-based compound semiconductor composition.

[0020] Another object of the present invention is to provide a compact of the above-mentioned novel SnS-based compound semiconductor composition or a thermoelectric material containing the compact.

[0021] In addition, the "SnS-based compound semiconductor composition" in this application includes both p-type and n-type, unless otherwise specified. [Means for solving the problem]

[0022] The present inventors have intensively studied the relationship between the lattice constant and the band gap of SnS compounds, and as a result have surprisingly found for the first time that, while in normal compounds, the band gap decreases as the lattice constant increases, in SnS compounds having a rectangular crystal structure, the band gap also increases as the lattice constant increases. 2+ The inventors have found that if an SnS-based compound semiconductor composition is manufactured by doping it with divalent cation atoms (e.g., Ca atoms, Sr atoms, Ba atoms) having an ionic radius larger than that of the SnS compound, thereby increasing only the lattice constant without changing the crystal structure, the band gap of the resulting composition will be larger than the band gap of the SnS compound (approximately 1.3 to 1.4 eV).

[0023] Incidentally, Non-Patent Document 1 states that Sn 1-x (II) xAlthough an S(II=Mg, Ca, Sr) alloy is disclosed, this alloy changes the crystal structure of the SnS compound from an orthorhombic structure (i.e., an orthorhombic crystal structure) to a rock salt structure (i.e., a rock salt type crystal structure) (i.e., a change from ortho-SnS to rs-SnS). In other words, Non-Patent Document 1 aims to induce a direct transition and make the band structure and optical properties more isotropic by changing the crystal structure of the alloy from an orthorhombic crystal structure to a rock salt type crystal structure, and does not include an SnS compound having an orthorhombic crystal structure. In addition, as can be understood from the fact that the thin film of the alloy in Non-Patent Document 1 also contains Mg, which reduces the lattice constant of the SnS compound having an orthorhombic crystal structure, it does not teach or suggest that in an SnS compound having an orthorhombic crystal structure, the band gap increases as the lattice constant increases. As far as the inventors know, the fact that in an SnS compound having a rectangular crystal structure, as the lattice constant increases, the band gap also increases, is something that was discovered for the first time by the inventors.

[0024] The present inventors have also found that, in the above-mentioned SnS-based compound semiconductor composition, an n-type SnS-based compound semiconductor composition can be obtained by further doping a halogen atom at the -2-valent S site in the SnS compound having an orthorhombic crystal structure.

[0025] Based on these findings, the present inventors have completed the present invention.

[0026] Specifically, the present invention has the following aspects. (Aspect 1) A SnS compound consisting of Sn atoms and S atoms and having a rectangular crystal structure, One or more types of atoms doped in the SnS compound; Including, At least one of the doping atoms is Sn 2+ is an atom that becomes a divalent cation having an ionic radius larger than the ionic radius of Compound semiconductor composition. (Aspect 2) Sn 2+ the atom that forms a divalent cation having an ionic radius larger than that of is one or more atoms selected from the group consisting of Ca atoms, Sr atoms, and Ba atoms. (Aspect 3) Sn 2+ 3. The composition according to claim 1 or 2, wherein the content of atoms forming divalent cations having an ionic radius larger than that of the compound semiconductor composition is 0.1 atomic % or more and less than 20 atomic % based on the compound semiconductor composition. (Aspect 4) The composition according to any one of Aspects 1 to 3, wherein the crystal structure belongs to space group Pnma, which is space group 62 of the International Tables for Crystallography. (Embodiment 5) The composition according to any one of embodiments 1 to 4, wherein the atoms doped in the SnS compound include one or more atoms selected from halogen atoms. (Embodiment 6) The composition according to any one of embodiments 1 to 4, wherein the atoms doped in the SnS compound include Cl atoms or Br atoms. (Aspect 7) The composition according to aspect 5 or 6, wherein the content of halogen atoms is 0.25 atomic % or more and 25 atomic % or less with respect to the compound semiconductor composition. (Embodiment 8) The composition according to any one of embodiments 5 to 7, which is an n-type semiconductor composition. (Embodiment 9) A thin film comprising the composition according to any one of embodiments 1 to 8. (Embodiment 10) A thin-film solar cell comprising the composition of any one of embodiments 1 to 8. (Embodiment 11) A top cell for a multijunction solar cell, comprising the composition of any one of embodiments 1 to 8. (Embodiment 12) A middle cell for a multijunction solar cell, comprising the composition according to any one of embodiments 1 to 8. (Embodiment 13) A multijunction solar cell comprising the composition of any one of embodiments 1 to 8. (Embodiment 14) The composition of any one of embodiments 1 to 8, which is in the form of a powder compact. (Embodiment 15) A thermoelectric material comprising the composition according to embodiment 14. (Aspect 16) (i) A metal target containing Sn or a tin halide, and Sn 2+ (ii) preparing a metal target containing an atom that will become a divalent cation having an ionic radius larger than that of Sn or a tin halide and irradiating the metal targets with Ar ions while supplying H2S gas; or 2+ The method for producing the thin film according to aspect 9 includes preparing a target containing a mixture of atoms that become divalent cations having an ionic radius larger than that of the target, and irradiating the target with Ar ions while supplying H2S gas. (Embodiment 17) A mixed powder of Sn or tin halide powder and S powder is added with Sn 2+ A sulfide powder containing an atom that becomes a divalent cation with an ionic radius larger than that of Sn 2+ and (c) adding an atomic ratio of 1:1 between Sn atoms and atoms that form divalent cations having an ionic radius larger than that of Sn, and filling the resulting mixture into a capsule for high pressure synthesis, and sintering the mixture at a high pressure of 20,000 atmospheres or more and at a high temperature of 600° C. or more to produce the composition according to embodiment 14. Effect of the Invention

[0027] According to the present invention, there is provided a method for producing a sintered body comprising the steps of: forming an SnS compound having a rectangular crystal structure composed of Sn atoms and S atoms; and doping the SnS compound with one or more kinds of atoms, wherein at least one of the doped atoms is Sn. 2+ It is therefore possible to provide a compound semiconductor composition in which the atoms form divalent cations having an ionic radius larger than that of the SnS-based compound semiconductor composition, thereby providing a novel SnS-based compound semiconductor composition that differs from existing SnS-based compound semiconductor compositions.

[0028] For example, the novel SnS-based compound semiconductor composition described above can be a SnS-based compound semiconductor composition having a band gap larger than 1.5 eV, which is the band gap of the SnS compound. 2+By appropriately adjusting the type and / or content of the atom that becomes a divalent cation having an ionic radius larger than that of the ionic radius of the SnS compound, the band gap can be easily controlled to a desired value according to the purpose of use. In addition, a solar cell having a configuration in which a SnS compound semiconductor composition having a band gap larger than 1.5 eV, which is the band gap of the SnS compound, is used as the above-mentioned novel SnS compound semiconductor composition and the SnS compound semiconductor composition is heterojunctioned with an n-type CdS compound semiconductor composition, can be confirmed to operate as a solar cell. Therefore, it can be said that the above-mentioned novel SnS compound semiconductor composition having a large band gap exceeding 1.5 eV is useful in designing a solar cell with a conversion efficiency of more than 40%.

[0029] Alternatively, as the above-mentioned novel SnS-based compound semiconductor composition, a p-type SnS-based compound semiconductor composition can be provided that can reduce the band offset at the interface between CdS and SnS (in other words, can be easily made n-type) even when it is heterojunctioned with an n-type CdS compound semiconductor composition. This makes it possible to achieve a higher conversion efficiency than before even in a solar cell constructed by heterojunctioning a p-type SnS compound semiconductor composition with an n-type CdS compound semiconductor composition.

[0030] Alternatively, the novel SnS-based compound semiconductor composition compound may be such that the atoms doped in the SnS compound are Sn 2+ In addition to an atom that becomes a divalent cation having an ionic radius larger than that of the SnS compound semiconductor composition, one or more kinds of atoms selected from halogen atoms are further contained, thereby providing a novel n-type SnS compound semiconductor composition that differs from existing n-type SnS compound semiconductor compositions. 2+By using an atom having a function of fixing the halogen atom (for example, any one of Ca atom, Sr atom, and Ba atom, or two or more of these atoms) as an atom that becomes a divalent cation having an ionic radius larger than that of the halogen atom, an n-type SnS-based compound semiconductor composition can be stably provided even under severe manufacturing conditions, and the yield can be increased compared to existing n-type SnS-based compound semiconductor compositions. As described above, according to the present invention, an n-type SnS-based compound semiconductor composition can be stably provided, and products using this n-type SnS-based compound semiconductor composition can be stably supplied regardless of the product form such as a thin film or a compact. In addition, by appropriately adjusting the type and / or content of the halogen atom, an n-type SnS-based compound semiconductor composition having the desired physical properties (for example, band gap and Seebeck coefficient) depending on the purpose of use can be easily obtained.

[0031] Alternatively, according to the present invention, a thin film, a thin film solar cell, a top cell for a multijunction solar cell, a middle cell for a multijunction solar cell, or a multijunction solar cell, containing the above-mentioned novel SnS-based compound semiconductor composition, can be provided. As described above, an SnS-based compound semiconductor composition having a band gap larger than 1.5 eV, which is the band gap of the SnS compound, can be provided, so that it is particularly useful for multijunction solar cells, which was originally difficult to achieve with SnS compound semiconductors.

[0032] Alternatively, according to the present invention, there can be provided a compact of the above-mentioned novel SnS-based compound semiconductor composition, or a thermoelectric material (for example, a thermoelectric element) containing this compact.

[0033] Alternatively, as described above, the n-type SnS-based compound semiconductor composition according to the present invention can increase the yield, and therefore a stable supply of devices using it (for example, thin-film solar cells and thermoelectric materials) can be expected.

[0034] Alternatively, as described above, the n-type SnS-based compound semiconductor composition according to the present invention can eliminate the band offset at both interfaces by homojunction with a p-type SnS compound, and is therefore highly useful in semiconductor devices.

[0035] As described above, the SnS-based compound semiconductor composition according to the present invention can provide a composition having a band gap larger than that of the SnS compound, and the band gap can be controlled to a desired band gap depending on the purpose of use, and can be made into a thin film as necessary. Therefore, when the SnS-based compound semiconductor composition according to the present invention is combined with, for example, a single crystal silicon solar cell to provide a multi-junction solar cell, a conversion efficiency (preferably 40% or more) that exceeds the conventional conversion efficiency of only about 5% can be achieved by using the SnS-based compound semiconductor composition having a band gap larger than that of the SnS compound and desired for the multi-junction solar cell. [Brief description of the drawings]

[0036] [Figure 1] FIG. 1 is a diagram showing an apparatus used for forming a thin film of the compound semiconductor composition of the present invention and a conceptual diagram of the process. [Diagram 2] 2 is a diagram showing X-ray diffraction patterns of a compound semiconductor composition in which a SnS compound having an orthorhombic crystal structure is doped with Ca atoms at various concentrations (0.3 atomic %, 0.8 atomic %, 1.7 atomic %, 2.7 atomic %, 4.2 atomic %, and 11.8 atomic %), and a compound semiconductor composition in which a SnS compound having an orthorhombic crystal structure is doped with Ba atoms at various concentrations (5.4 atomic %, 13.4 atomic %, and 14.6 atomic %). In the diagram, at% means atomic %. [Diagram 3] 3 is a diagram showing Raman spectra of a compound semiconductor composition in which a SnS compound having a rectangular crystal structure is not doped with Ca atoms and a compound semiconductor composition in which the SnS compound is doped with 0.8 atomic % of Ca atoms. In the figure, at % means atomic %. [Figure 4]Fig. 4 shows the Tauc plots and band gaps of a compound semiconductor composition formed into a thin film, in which a SnS compound having a rectangular crystal structure is not doped with Ca atoms and a compound semiconductor composition in which the SnS compound is doped with Ca atoms at various concentrations (4.2 atomic % and 11.8 atomic %). In the figure, at% means atomic %. [Diagram 5] 5 is a diagram showing the Tauc plots and band gaps of a compound semiconductor composition formed into a thin film, in which a SnS compound having a rectangular crystal structure is not doped with Ba atoms and the SnS compound is doped with Ba atoms at various concentrations (5.4 atomic %, 13.4 atomic %, and 14.6 atomic %). In the figure, at% means atomic %. [Figure 6] 6 is a diagram showing X-ray diffraction of compound semiconductor compositions in which a SnS compound having a rectangular crystal structure is doped with Sr atoms at various concentrations (1.2 atomic % and 8.6 atomic %). In the figure, at% means atomic %. [Figure 7] 7 is a diagram showing the Tauc plots and band gaps of a compound semiconductor composition formed into a thin film, in which a SnS compound having an orthorhombic crystal structure is not doped with Sr atoms and a compound semiconductor composition in which the SnS compound is doped with Sr atoms at various concentrations (1.2 atomic % and 4.9 atomic %). In the figure, at% means atomic %. [Figure 8] 8 is a diagram summarizing the physical properties of various compound semiconductor compositions when thin films of the compound semiconductor compositions are formed by doping a SnS compound having an orthorhombic crystal structure with Ca atoms, Ba atoms, or Sr atoms at various concentrations according to the later-described manufacturing method 1. In the diagram, at% means atomic %. [Figure 9] FIG. 9 is a conceptual diagram of an apparatus used to confirm the band offset at a heterojunction interface between a compound semiconductor composition in which a SnS compound having a rectangular crystal structure is doped with Ba atoms, and an n-type CdS compound semiconductor composition. [Figure 10]FIG. 10 is a diagram showing the analysis results of VBMEF(BTS), which is the energy level at the upper end of the valence band, and CBMEF(BTS), which is the energy level at the lower end of the conduction band, of a SnS compound doped with Ba atoms (also referred to as “BTS” in this application), and VBMEF(CdS), which is the energy level at the upper end of the valence band, and CBMEF(CdS), which is the energy level at the lower end of the conduction band, of a CdS compound. [Figure 11] FIG. 11 is a diagram showing the electron affinity and ionization potential between a CdS compound and a SnS-based compound doped with Ba atoms (BTS) when it is assumed that the electron affinity of the CdS compound is 4.1 eV. [Figure 12] 12 is a diagram showing the Cl atom content (atomic %) incorporated in each compound semiconductor composition when a thin film of a compound semiconductor composition in which a SnS compound having an orthorhombic crystal structure is doped with Cl atoms at various concentrations without doping with Ca atoms and a thin film of a compound semiconductor composition in which the SnS compound is doped with Ca atoms and Cl atoms at various concentrations according to Production Method 2 described below are formed. In the figure, at% means atomic %. [Figure 13] FIG. 13 is a graph showing the Seebeck coefficient (unit: μV / K) and the change over time of the Seebeck coefficient when a thin film of a compound semiconductor composition is formed by doping a SnS compound having a rectangular crystal structure with Ca atoms and Cl atoms according to Manufacturing Method 3 described later and an SnCl4 solution of the compound semiconductor composition is dropped onto the compound semiconductor composition. [Figure 14] FIG. 14 shows a high-pressure synthesis apparatus used to manufacture the green compact and a conceptual diagram of the process. [Figure 15] FIG. 15 is a diagram showing an apparatus and a conceptual diagram of the process used to form a thin film of a Ba-Sn-S-Br compound semiconductor composition (a compound semiconductor composition composed of Ba, Sn, S, and Br), which is one embodiment of the present invention. [Figure 16]FIG. 16 is a graph showing the Seebeck coefficient (unit: μV / K) and change over time of the Seebeck coefficient of each compound semiconductor composition when a thin film of a compound semiconductor composition in which a SnS compound having a rhombic crystal structure is doped with 2 atomic % of Ca atoms ("Ca (2 atomic %)-SnS" in the figure) and a thin film of a compound semiconductor composition in which a SnS compound having a rhombic crystal structure is not doped with Ca atoms ("Undoped: SnS" in the figure) are formed according to Manufacturing Method 6 described below. [Figure 17] FIG. 17 is a schematic diagram showing the structure of a solar cell manufactured according to Manufacturing Method 7 described below. [Figure 18] FIG. 18 is a graph showing the output characteristics (i.e., JV characteristics) of a solar cell having a structure in which a 800 nm thin film (Ba-SnS film) of an SnS-based compound semiconductor composition, in which a SnS compound having a rectangular crystal structure is doped with Ba atoms, is heterojunctioned with a CdS compound semiconductor composition. [Figure 19] FIG. 19 is a graph plotting the conversion efficiency (%) of a solar cell having a structure in which a thin film (Ca-SnS film) of an SnS-based compound semiconductor composition obtained by doping a SnS compound having an orthorhombic crystal structure with Ca atoms is heterojunctioned with a CdS compound semiconductor composition, a solar cell having a structure in which a thin film (Sr-SnS film) of an SnS-based compound semiconductor composition obtained by doping a SnS compound having an orthorhombic crystal structure with Sr atoms is heterojunctioned with a CdS compound semiconductor composition, and a solar cell having a structure in which a thin film (Ba-SnS film) of an SnS compound having an orthorhombic crystal structure with Ba atoms is heterojunctioned with a CdS compound semiconductor composition, against the thickness of each thin film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0037] Hereinafter, the embodiments of the present invention will be described in detail. Note that the present invention is not limited to the following embodiments, and can be modified in various ways within the scope of the present invention.

[0038] One aspect of the present invention is a method for producing a crystalline SnS compound having a rectangular crystal structure composed of Sn atoms and S atoms, and one or more types of atoms doped into the SnS compound, wherein at least one of the doped atoms is Sn. 2+ The compound semiconductor composition is an atom that becomes a divalent cation having an ionic radius larger than the ionic radius of the compound semiconductor composition.

[0039] In the compound semiconductor composition described above, the SnS compound consisting of Sn and S atoms has a cubic crystal structure. Specifically, this crystal structure is a crystal structure expressed as Pnma, which belongs to space group 62 in the "International Tables for Crystallography," a handbook compiled by the International Union of Crystallography.

[0040] In the present invention, the SnS compound constituting the compound semiconductor composition has a rectangular crystal structure. This is because at least one of the atoms doped in the SnS compound is Sn. 2+ This means that even if the atom becomes a divalent cation with an ionic radius larger than that of Sn, the crystal structure does not change and the orthorhombic crystal structure is maintained. 2+ A divalent cation atom having an ionic radius larger than the ionic radius of Sn is doped into the +2 valent Sn site in the SnS compound having a rectangular crystal structure. In the present invention, at least one of the atoms doped into the SnS compound is Sn 2+ Even when the atoms become divalent cations with an ionic radius larger than that of the SnS compound, the lattice constant merely increases, and the crystal structure itself does not change, and the orthorhombic crystal structure of the SnS compound is maintained as is.

[0041] In the present invention, "doping" means adding a small amount of an impurity to change the physical properties of the crystal.

[0042] In the above-mentioned compound semiconductor, "at least one of the doped atoms" (i.e., at least one of the atoms doped in the SnS compound) is Sn 2+ In other words, at least one of the atoms doped in the SnS compound is an atom that becomes a divalent cation having an ionic radius larger than the ionic radius of Sn in the SnS compound having a rectangular crystal structure. 2+ There are no particular limitations on the type of atom that can be used as long as it is an atom that can form a divalent cation having an ionic radius larger than 0.93 Å, which is the ionic radius of 1.0 nm. For example, a SnS compound has 6 Sn coordinates, but a Ca compound with the same coordination number is not particularly limited. 2+ The ionic radius of Sr is 1.00 Å. 2+ The ionic radius of Ba is 1.18 Å. 2+ The ionic radius of Sn is 1.35 Å. 2+ Since the ionic radius of these atoms is larger than that of the ionic radius of the cations ... 2+ The ionic radius of Sn is 0.72 Å. 2+ and the desired band gap in the present invention is not obtained. Therefore, it does not fall under the above-mentioned "at least one kind of atom doped in the SnS compound."

[0043] The compound semiconductor composition of the present invention preferably has a band gap of 1.5 eV or more, which is larger than the band gap of the SnS compound.

[0044] In the compound semiconductor composition of the present invention, "Sn 2+ The content of "atoms that become divalent cations having an ionic radius larger than the ionic radius of the cation" is not particularly limited as long as the object of the present invention can be achieved. For example, in order to control the band gap to a desired value depending on the purpose of use, it is preferable to set it to the following range. In the compound semiconductor composition of the present invention, "Sn 2+ The lower limit of the content of "atoms which become divalent cations having an ionic radius larger than that of" is preferably 0.1 atomic % or more, more preferably 1.0 atomic % or more, even more preferably 4.0 atomic % or more, and even more preferably 5.0 atomic % or more, relative to the compound semiconductor composition. The upper limit is preferably less than 20 atomic %, more preferably 15 atomic % or less, even more preferably 12 atomic % or less, and even more preferably 10 atomic % or less, relative to the compound semiconductor composition. Incidentally, it is preferable to set the upper limit to less than 20 atomic % in order to avoid the possibility that the crystal system changes and the crystallinity decreases, resulting in a deterioration in electrical characteristics, which is particularly preferable in order to obtain a solar cell with high efficiency.

[0045] For example, when the compound semiconductor composition of the present invention is applied in combination with a single crystal silicon solar cell using a silicon single crystal having a band gap of 1.1 eV, the lower limit of the band gap of the compound semiconductor composition of the present invention is preferably 1.5 eV or more, more preferably 1.6 eV or more, and even more preferably 1.8 eV or more. The upper limit of the band gap of the compound semiconductor composition of the present invention is preferably 3.2 eV or less, more preferably 2.6 eV or less, even more preferably 2.3 eV or less, even more preferably 2.0 eV or less, even more preferably 1.9 eV or less, and even more preferably 1.8 eV or less. As described above, when it is desired to control the band gap to a desired value depending on the purpose of use, Sn 2+ In this case, the type and / or content of atoms that become divalent cations having an ionic radius larger than that of the ionic radius of the cation may be appropriately adjusted.

[0046] When "at least one of the doped atoms of the SnS compound" in the compound semiconductor composition of the present invention is a Ca atom, the lower limit of the Ca atom content (i.e., the doping amount) is preferably 0.1 atomic % or more, more preferably 4.0 atomic % or more, relative to the compound semiconductor composition, and the upper limit is preferably less than 20 atomic %, more preferably 12 atomic % or less, relative to the compound semiconductor composition. The band gap of the compound semiconductor composition satisfies the range of 1.55 eV to 1.89 eV when the Ca atom content is within the range of 0.1 atomic % to less than 20 atomic %, and the band gap of the compound semiconductor composition satisfies the range of 1.6 eV to 1.8 eV when the Ca atom content is within the range of 4.0 atomic % to 12 atomic %, and the lattice spacing at this time satisfies the range of 2.82 Å to 2.86 Å.

[0047] When "at least one of the doped atoms of the SnS compound" in the compound semiconductor composition of the present invention is Ba atom, the lower limit of the content of Ba atom (i.e., doping amount) is preferably 0.1 atomic % or more, more preferably 5.0 atomic % or more, relative to the compound semiconductor composition, and the upper limit is preferably less than 20 atomic %, more preferably 15 atomic % or less, relative to the compound semiconductor composition. The band gap of the compound semiconductor composition satisfies the range of 1.55 eV to 2.51 eV when the content of the Ba atoms is within the range of 0.1 atomic % to less than 20 atomic %, and the band gap of the compound semiconductor composition satisfies the range of 1.8 eV to 2.3 eV when the content of the Ba atoms is within the range of 5.0 atomic % to 15 atomic %, and the lattice spacing at this time satisfies the range of 2.85 Å to 2.92 Å.

[0048] When "at least one of the doped atoms (i.e., the SnS compound)" in the compound semiconductor composition of the present invention is Sr atom, the lower limit of the content of this Sr atom (i.e., the doping amount) is preferably 0.1 atomic % or more, more preferably 1.0 atomic % or more, relative to the compound semiconductor composition. The upper limit is preferably less than 20 atomic %, more preferably 10 atomic % or less, relative to the compound semiconductor composition. The band gap of the compound semiconductor composition satisfies the range of 1.55 eV to 3.15 eV when the content of the Sr atoms is within the range of 0.1 atomic % to less than 20 atomic %, and the band gap of the compound semiconductor composition satisfies the range of 1.8 eV to 2.0 eV when the content of the Sr atoms is within the range of 1.0 atomic % to 10 atomic %, and the lattice spacing at this time satisfies the range of 2.82 Å to 2.88 Å.

[0049] One aspect of the present invention is a method for producing a crystalline SnS compound having a rectangular crystal structure composed of Sn atoms and S atoms, and one or more types of atoms doped into the SnS compound, wherein at least one of the doped atoms is Sn. 2+ The compound semiconductor composition may further include a compound semiconductor composition in which the atoms doped in the SnS compound are atoms that become divalent cations having an ionic radius larger than that of the SnS compound, and the atoms doped in the SnS compound may further include one or more kinds of atoms selected from halogen atoms.

[0050] In this way, it is preferable for providing an n-type SnS-based compound semiconductor composition that the atoms doped in the SnS compound further include one or more types of atoms selected from halogen atoms.

[0051] The halogen atom refers to an atom belonging to Group 17 of the periodic table, such as F, Cl, Br, or I. As the halogen atom, Cl atom and Br atom are preferable, and Cl atom is more preferable.

[0052] The halogen atoms have a structure in which the halogen atoms are doped into the divalent S site of the SnS compound having an orthorhombic crystal structure, and in this case, the crystal structure of the SnS compound is maintained as an orthorhombic crystal structure.

[0053] The content of the halogen atoms in the compound semiconductor composition of the present invention is not particularly limited as long as the object of the present invention can be achieved. For example, in order to obtain an n-type SnS compound semiconductor composition having desired physical properties (e.g., band gap and Seebeck coefficient) depending on the purpose of use, it is preferable to set the content within the following range.

[0054] The lower limit of the content of the halogen atoms in the compound semiconductor composition of the present invention is preferably 0.25 atomic % or more, more preferably 0.5 atomic % or more, and even more preferably 0.5 atomic % or more, relative to the compound semiconductor composition, and the upper limit is preferably 25 atomic % or less, more preferably 10 atomic % or less, and even more preferably 5 atomic % or less, relative to the compound semiconductor composition.

[0055] When the SnS compound in the compound semiconductor composition of the present invention contains one or more atoms selected from halogen atoms, the above-mentioned "Sn 2+ It is preferable that the "atom that becomes a divalent cation having an ionic radius larger than the ionic radius of Sn" also has a function of fixing the halogen atom. For example, from the viewpoint of the stability of the function of fixing the halogen atom (especially Cl atom), "Sn 2+ The "atom that becomes a divalent cation having an ionic radius larger than that of" is more preferably any one of Ca, Sr, and Ba atoms, or two or more of these atoms. In this case, the halogen atom is stably fixed in the crystal lattice of the SnS compound, which is composed of Sn and S atoms and has an orthorhombic crystal structure. Therefore, even under severe manufacturing conditions, an n-type SnS-based compound semiconductor composition can be stably provided, and the yield is higher than that of existing n-type SnS-based compound semiconductor compositions.

[0056] One aspect of the present invention is a thin film containing the compound semiconductor composition. The method for forming the thin film is not particularly limited as long as the object of the present invention can be achieved, and examples of the method include a method using an RF magnetron sputtering device, a vapor deposition method, a chemical bath deposition method (CBD), and a spray pyrolysis method. When an RF magnetron sputtering device is used, the thin film is formed by depositing a metal target containing Sn or a tin halide as a target and a tin halide as a target. 2+ The tin oxide may be produced by preparing a metal target containing an atom that will become a divalent cation having an ionic radius larger than that of the target, and irradiating both metal targets with Ar ions while supplying H2S gas. Alternatively, the tin oxide may be produced by using Sn or a tin halide as a target and Sn 2+ Alternatively, a target containing a mixture of atoms that will become divalent cations having an ionic radius larger than that of the target and Ar ions may be prepared, and the target may be irradiated with Ar ions while being supplied with H2S gas. The thin film of the present invention may be made entirely or partially using the compound semiconductor composition.

[0057] One aspect of the present invention is a thin-film solar cell containing the compound semiconductor composition. The solar cell is a solar cell in which a thin film of the compound semiconductor composition of the present invention is formed on a substrate such as quartz glass. Thin-film solar cells have advantages such as lower manufacturing costs and flexibility compared to conventional crystalline silicon solar cells. The thin-film solar cell of the present invention may be one in which the compound semiconductor composition is used in part or in whole.

[0058] One aspect of the present invention is a top cell or middle cell for a multijunction solar cell, which contains the compound semiconductor composition, thereby providing a multijunction solar cell. Examples of multijunction solar cells include a three-junction solar cell formed by joining three cells, a bottom cell, a middle cell, and a top cell, and a two-junction solar cell formed by joining a cell formed by combining the middle cell and the top cell with a bottom cell. The bottom cell is required to absorb light on the long wavelength side belonging to the deep red to infrared region (about 730 to 1240 nm) of sunlight (i.e., a band gap of about 1 eV), the middle cell is required to absorb light with wavelengths belonging to the yellow to red region (about 495 to 730 nm) (i.e., a band gap of about 1.7 eV), and the top cell is required to absorb light on the short wavelength side belonging to the blue to green region (about 460 to 495 nm) (i.e., a band gap of about 2.5 eV).

[0059] As described above, the compound semiconductor composition of the present invention provides an SnS-based compound semiconductor composition having a band gap in the range of 1.5 eV to 3.2 eV, which is sufficiently larger than the band gap of silicon (1.1 eV). As described above, the band gap value of the compound semiconductor composition of the present invention is 2+The ionic radius of the divalent cation having an ionic radius larger than that of the ionic radius of the halogen atom is appropriately adjusted to a desired value according to the intended use by appropriately adjusting the type and / or content of the atom (including the type and / or content of the halogen atom in the case where one or more types of atoms selected from halogen atoms are included). Therefore, in the present invention, as a multi-junction solar cell, for example, a two-junction solar cell using a single crystal silicon solar cell, which is widely used in general, as a bottom cell, and a SnS-based compound semiconductor composition, which is the compound semiconductor composition of the present invention, with a band gap adjusted to about 1.7 eV, as a top cell, or a three-junction solar cell using a single crystal silicon solar cell as a bottom cell, a SnS-based compound semiconductor composition, which is the compound semiconductor composition of the present invention, with a band gap adjusted to about 1.7 eV, as a middle cell, and a compound semiconductor with a band gap of about 2.5 eV, as a top cell, is provided.

[0060] In one aspect of the present invention, the compound semiconductor composition of the present invention is in the form of a powder compact. The method for producing the powder compact is not particularly limited as long as the object of the present invention can be achieved. For example, there is a method for producing the powder compact using a high-pressure synthesis apparatus or a spark plasma sintering method (SPS).

[0061] One aspect of the present invention is a thermoelectric material containing the powder compact. As described above, a thermoelectric material is a solid material that has the property of converting thermal energy into electrical energy and vice versa. For example, the thermoelectric material is made into a thermoelectric conversion element and used as a power generation device or a thermoelectric power generation module for use in various electronic devices. The thermoelectric material of the present invention may be made entirely or partially using the powder compact.

[0062] There are no particular limitations on the conditions not specified in this application as long as the object of the present invention can be achieved. EXAMPLES

[0063] Next, the embodiment of the present invention will be described in more detail with reference to examples. However, the embodiment of the present invention is not limited to the following examples as long as it does not depart from the gist of the invention.

[0064] <Manufacturing method 1> A thin film of a compound semiconductor containing an SnS compound having a rectangular crystal structure composed of Sn atoms and S atoms and one type of atom doped in the SnS compound, at least one of the doped atoms being a Ca atom, a Sr atom, or a Ba atom, was formed by the following method. The doped Ca atom, Sr atom, or Ba atom is, as described above, Sn 2+ These are atoms that form divalent cations with an ionic radius larger than that of the cation of

[0065] The equipment used for the above-mentioned film formation and a conceptual diagram of the process are shown in Figure 1. For the deposition, an RF (radio frequency) magnetron sputtering device (manufactured by Pascal) was used. As shown in FIG. 1, the target is provided with three independent cathodes, and three types of targets can be used simultaneously, but in this manufacturing method, two of these types were used. Specifically, two types of targets were used: a target made of Sn metal and a target made of Ca, Sr, or Ba metal. The target made of Sn metal and SnCl2 powder pressed and solidified as shown in FIG. 1 is used in the "manufacturing method 2" described later. The targets are not limited to the two types described above, and may be a mixture of Sn metal and Ca metal, Sr metal, or Ba metal to be used as one type of target. Each target had a size of 1 inch (=2.54 cm). H2S gas was used as the source of S atoms and was supplied at a flow rate of 0.5 to 1.0 sccm (sccm = ml / min). Ar was used as the process gas. Synthetic quartz glass was used for the substrate. The film formation temperature was 270 to 320°C, the film formation time was 20 minutes, and the total pressure in the apparatus was 0.7 Pa. The Sn metal target and H2S gas were used as the sources of Sn atoms and S atoms of the SnS compound, respectively, and a Ca metal, Sr metal, or Ba metal target was used as the source of the doped metal atoms.

[0066] (Example 1-1) Thin films of compound semiconductor compositions were formed by doping the SnS compound having an orthorhombic crystal structure with Ca atoms at various concentrations according to the above-mentioned manufacturing method 1. The doping concentration of Ca atoms was achieved by changing the RF power applied to each target. The doping concentration of Ca atoms means the content of Ca atoms in the compound semiconductor composition formed into a thin film (i.e., the doping amount), and in the present application, is expressed as atomic % with respect to the compound semiconductor composition, but atomic % may also be expressed as at %.

[0067] In the above film formation, the RF power applied to the target made of Sn metal was kept at 14 W. The RF power applied to the target made of Ca metal was changed from 5 to 35 W. The concentration of Ca atoms contained in the formed thin film was quantified by EDX (energy dispersive X-ray analysis) (Horiba, Ltd. EX-220). The crystal structure of each compound semiconductor composition formed into a thin film was identified using an X-ray diffraction (XRD) device (RIGAKU, RINT-2200). The results are shown in Figure 2. As shown in Figure 2, it was confirmed that each compound semiconductor composition formed into a thin film exhibited a very strong (111) orientation. In addition, it was confirmed that the interplanar spacing increased as the amount of doped Ca atoms increased, and that when the Ca atom content was in the range of 4 atomic % to 12 atomic %, the interplanar spacing was in the range of 2.82 Å to 2.86 Å.

[0068] The structure of the SnS-based compound semiconductor composition doped with Ca atoms was also evaluated by Raman spectroscopy. A Renishaw inVia Raman microscope was used as the Raman spectrometer. The results are shown in Figure 3. As shown in Figure 3, it was confirmed that both the thin film of the SnS compound not doped with Ca atoms and the thin film of the SnS compound doped with 0.8 atomic % of Ca atoms have the same SnS(Pnma) structure (i.e., a rectangular crystal structure). This shows that the change caused by doping with Ca atoms is only in the lattice constant, and there is no change in the crystal structure.

[0069] In addition, for the SnS compound consisting of Sn atoms and S atoms (i.e., the SnS compound not doped with Ca) and each SnS compound doped with Ca at 4.2 atomic % and 11.8 atomic % respectively, the band gaps of these compound semiconductor compositions formed into thin films were calculated from the Tauc plot. The Tauc plot was calculated from the absorption and reflection spectra obtained by a spectrophotometer (Solid spec3200 DUV manufactured by Shimadzu Corporation). The results are shown in Figure 4. 4, the band gap was 1.55 eV when Ca atoms were not doped, 1.60 eV when Ca atoms were doped at 4.2 atomic %, and 1.75 eV when Ca atoms were doped at 11.8 atomic %. Incidentally, the theoretical value of the band gap when Ca atoms were not doped is about 1.3 eV, but the value calculated from the Tauc plot in this example was 1.55 eV, which is understood to be a simple measurement error caused by the influence of tensile stress from the substrate, etc. As shown in FIG. 4, it was confirmed that the band gap increases as the amount of doped Ca atoms increases, and when the amount reaches 11.8 atomic %, the band gap expands to 1.75 eV.

[0070] As described above, this band gap of 1.75 eV satisfies the band gap (about 1.7 eV) required for an SnS-based compound semiconductor composition in a multi-junction solar cell using a single crystal silicon solar cell as the bottom cell, a two-junction solar cell using an SnS-based compound semiconductor composition in the top cell, and a three-junction solar cell using an SnS-based compound semiconductor composition in the middle cell. This fact is due to the fact that the SnS compound having a rectangular crystal structure contains Sn atoms such as Ca atoms. 2+This means that by doping an atom that becomes a divalent cation having an ionic radius larger than that of SnS, a compound semiconductor composition that is effective as a top cell or a middle cell for a multi-junction solar cell using a single crystal silicon solar cell as a bottom cell can be obtained, and a multi-junction solar cell can be provided using the SnS-based compound semiconductor composition. As a result, it was found that a conversion efficiency higher than the conversion efficiency of conventional SnS solar cells, which was only about 5%, can be achieved.

[0071] (Example 1-2) Thin films of compound semiconductor compositions were formed by doping the SnS compound having a rectangular crystal structure with Ba atoms at various concentrations according to the above-mentioned manufacturing method 1. The doping concentration of Ba atoms was achieved by changing the RF power applied to each target. The doping concentration of Ba atoms means the content (i.e., doping amount) of Ba atoms in the compound semiconductor composition formed into a thin film, and in the present application, is expressed as atomic % with respect to the compound semiconductor composition, but atomic % may also be expressed as at %.

[0072] During the above film formation, the RF power applied to the target made of Sn metal was kept at 14 W. The RF power applied to the target made of Ba metal was varied from 5 to 35 W. The concentration of Ba atoms contained in the formed thin film was quantified by EDX (energy dispersive X-ray analysis) (Horiba, Ltd. EX-220). The lattice constant of each compound semiconductor composition formed into a thin film was identified using an X-ray diffraction (XRD) device (RIGAKU, Ltd. RINT-2200). The results are shown in Figure 2. As shown in Figure 2, it was confirmed that each compound semiconductor composition formed into a thin film exhibited a very strong (111) orientation. In addition, it was confirmed that the interplanar spacing increased as the amount of doped Ba atoms increased, and that when the Ba atom content was in the range of 5 atomic % to 15 atomic %, the interplanar spacing was in the range of 2.85 Å to 2.92 Å.

[0073] The structure of the SnS-based compound semiconductor composition doped with Ba atoms was also evaluated by Raman spectroscopy using a Renishaw inVia Raman microscope. It was confirmed that both the thin film of the SnS compound not doped with Ba atoms and the thin film of the SnS compound doped with Ba atoms have the same SnS(Pnma) structure (i.e., a rectangular crystal structure) (not shown). This shows that the change caused by doping with Ba atoms is only the lattice constant, and there is no change in the crystal structure.

[0074] In addition, for each SnS-based compound doped with Ba atoms at 5.4 atomic %, 13.4 atomic %, and 14.6 atomic %, the band gap of these compound semiconductor compositions formed into thin films was calculated from the Tauc plot. The Tauc plot was calculated from the absorption and reflection spectra obtained by a spectrophotometer (Solid spec3200 DUV, manufactured by Shimadzu Corporation). The results are shown in Figure 5. For comparison, FIG. 5 also shows the Tauc plot and band gap (1.55 eV) of the SnS compound consisting of Sn atoms and S atoms shown in FIG. 4 as an SnS compound not doped with Ba atoms. As shown in Figure 5, the band gap is 1.8 eV when Ba atoms are doped at 5.4 atomic %, 2.15 eV when Ba atoms are doped at 13.4 atomic %, and 2.25 eV when Ba atoms are doped at 14.6 atomic %. It was confirmed that the band gap increases as the amount of Ba atoms doped increases, and at 14.6 atomic %, the band gap expands to 2.25 eV.

[0075] As described above, this band gap of 2.25 eV is close to the band gap (about 2.5 eV) required for using an SnS-based compound semiconductor composition in the top cell in a triple-junction solar cell using a single crystal silicon solar cell as the bottom cell, and it has been confirmed that this is a promising top cell. Although not shown, it has been confirmed that the band gap can be expanded to 2.51 eV by increasing the amount of Ba atoms to be doped up to 20 atomic % (but less than 20 atomic %). This value satisfies the above-mentioned band gap (about 2.5 eV) required for the SnS-based compound semiconductor composition. Furthermore, the band gap of 1.8 eV when doped with 5.4 atomic % Ba atoms is a value that satisfies the band gap (approximately 1.7 eV) required for an SnS-based compound semiconductor composition in a multi-junction solar cell that uses a single crystal silicon solar cell as the bottom cell, as described above, in a two-junction solar cell that uses an SnS-based compound semiconductor composition in the top cell, or a three-junction solar cell that uses an SnS-based compound semiconductor composition in the middle cell. These facts indicate that the SnS compound having a rectangular crystal structure contains Sn atoms such as Ba atoms. 2+ This means that by doping an atom that becomes a divalent cation having an ionic radius larger than that of a SnS-based compound semiconductor composition that is effective as a top cell or a middle cell for a multi-junction solar cell using a single crystal silicon solar cell as a bottom cell, a SnS-based compound semiconductor composition can be obtained, and a multi-junction solar cell can be provided using this SnS-based compound semiconductor composition. As a result, it was found that a conversion efficiency higher than the conversion efficiency of conventional SnS solar cells, which was only about 5%, can be achieved.

[0076] (Examples 1-3) Thin films of compound semiconductor compositions were formed by doping the SnS compound having an orthorhombic crystal structure with Sr atoms at various concentrations according to the above-mentioned manufacturing method 1. The doping concentration of Sr atoms was achieved by changing the RF power applied to each target. The doping concentration of Sr atoms means the content of Sr atoms in the compound semiconductor composition formed into a thin film (i.e., the doping amount), and in the present application, is expressed as atomic % with respect to the compound semiconductor composition, but atomic % may also be expressed as at %.

[0077] During the above film formation, the RF power applied to the Sn metal target was maintained at 14 W. The RF power applied to the Sr metal target was varied from 5 to 35 W. The concentration of Sr atoms contained in the formed thin film was quantified using EDX (energy dispersive X-ray analysis) (Horiba, Ltd. EX-220). The crystal structure of each compound semiconductor composition formed into a thin film was identified using an X-ray diffraction (XRD) device (RIGAKU, Ltd. RINT-2200). The results are shown in Figure 6. As shown in Figure 6, it was confirmed that each compound semiconductor composition formed into a thin film exhibited a very strong (111) orientation, and that the interplanar spacing increased as the amount of doped Sr atoms increased. Although not shown in the figure, it was confirmed that the interplanar spacing was in the range of 2.82 Å to 2.88 Å when the content of Sr atoms was in the range of 1.0 atomic % to 10 atomic %.

[0078] The structure of the Sr-doped SnS-based compound semiconductor composition was also evaluated by Raman spectroscopy using a Renishaw inVia Raman microscope. It was confirmed that both the thin film of the SnS compound not doped with Sr atoms and the thin film of the SnS compound doped with Sr atoms have the same SnS(Pnma) structure (i.e., a rectangular crystal structure) (not shown). This shows that the change caused by doping with Sr atoms is only the lattice constant, and there is no change in the crystal structure.

[0079] In addition, for each SnS-based compound doped with 1.2 atomic % and 4.9 atomic % Sr atoms, the band gap of these compound semiconductor compositions formed into a thin film was calculated from the Tauc plot. The Tauc plot was calculated from the absorption and reflection spectra obtained by a spectrophotometer (Solid spec3200 DUV, manufactured by Shimadzu Corporation). The results are shown in Figure 7. For comparison, FIG. 7 also shows the Tauc plot and band gap (1.55 eV) of the SnS compound consisting of Sn atoms and S atoms shown in FIG. 4 as an SnS compound not doped with Sr atoms. As shown in Fig. 7, the band gap is 1.8 eV when Sr atoms are doped at 1.2 atomic %, and 1.95 eV when Sr atoms are doped at 4.9 atomic %, and it was confirmed that the band gap becomes larger as the amount of Sr atoms doped increases, and when the amount is 4.9 atomic %, the band gap expands to 1.95 eV. Comparing with Fig. 4 and 5, it was confirmed that the expansion of the band gap due to the doping amount of Sr atoms is larger than when Ca atoms or Ba atoms are doped.

[0080] As described above, this band gap of 1.95 eV satisfies the band gap (approximately 1.7 eV) required for an SnS-based compound semiconductor composition in a multi-junction solar cell that uses a single crystal silicon solar cell as the bottom cell, a two-junction solar cell that uses an SnS-based compound semiconductor composition in the top cell, or a three-junction solar cell that uses an SnS-based compound semiconductor composition in the middle cell. In addition, although not shown, it was confirmed that the band gap can be expanded to 3.15 eV by increasing the amount of doped Sr up to 20 atomic % (but less than 20 atomic %), which is a value that fully satisfies the above-mentioned band gap (about 2.5 eV) required for SnS-based compound semiconductor compositions. These facts indicate that the SnS compound, which has a rectangular crystal structure, contains Sn atoms such as Sr atoms. 2+This means that by doping an atom that becomes a divalent cation having an ionic radius larger than that of a SnS-based compound semiconductor composition that is effective as a top cell or a middle cell for a multi-junction solar cell using a single crystal silicon solar cell as a bottom cell, a SnS-based compound semiconductor composition can be obtained, and a multi-junction solar cell can be provided using this SnS-based compound semiconductor composition. As a result, it was found that a conversion efficiency higher than the conversion efficiency of conventional SnS solar cells, which was only about 5%, can be achieved.

[0081] Fig. 8 is a table summarizing the physical properties (specifically, the interplanar spacing (111), band gap, and lattice constant change) of various compound semiconductor compositions when thin films of the compound semiconductor compositions are formed by doping the SnS compound having a rectangular crystal structure with Ca atoms, Ba atoms, or Sr atoms at various doping concentrations (atomic %) according to the above-mentioned manufacturing method 1. The doping amount of Sr atoms in Fig. 8 is an estimated value because the peak position of Sr overlaps with the peak position of S, and the doping amount was calculated based on the lattice constant change. It was confirmed that, compared to the case where Ca, Ba, or Sr atoms were not doped, the lattice constant and the interplanar spacing of the (111) plane increased by doping with Ca, Ba, or Sr atoms, and by increasing the doping amount, and the band gap also increased. It is understood that factors other than the ionic radius also contribute to the physical property results when Sr atoms are doped.

[0082] Next, an experiment was conducted to confirm that the band offset (specifically, valence band offset) at the junction interface between the SnS compound having a rectangular crystal structure and an n-type CdS compound semiconductor composition is reduced when the SnS compound is doped with Ba atoms to form a heterojunction with the n-type CdS compound semiconductor composition. A schematic diagram of the device used in the experiment is shown in Figure 9. In a glove box purged with Ar gas, a Ba-doped SnS-based compound was immersed in an ammonia solution to remove the carbon (C) and (O) adsorbed on the surface by surface treatment. The sample was then transferred to a load-lock chamber (LL) connected to an Ar-purged glove box, and lamp annealed in vacuum to remove water (HO) adsorbed on the surface and obtain a clean surface of the SnS-based compound doped with Ba atoms. The SnS-based compound doped with Ba atoms with a clean surface was transferred to an ultra-high vacuum through a vacuum transfer chamber connected to the LL chamber (<~10 -8 The researchers alternated between the deposition of CdS compounds by molecular beam epitaxy (MBE), various measurements (specifically ultraviolet photoelectron spectroscopy: UPS, inverse photoelectron spectroscopy: IPES, and X-ray photoelectron spectroscopy: XPS), and deposition of CdS compounds by molecular beam epitaxy (MBE). The valence band top and conductor bottom (band position) of CdS compounds have been investigated in detail, and by comparing with CdS compounds, it is possible to determine the band positions of SnS compounds doped with Ba atoms. By measuring UPS and IPES, it is possible to determine the top of the valence band (hereafter referred to as "VBM" or "VBM EF ") and the conduction band minimum (hereinafter referred to as "CBM" or "CBM EF By performing XPS measurements while depositing a CdS compound, the amount of band bending at the interface can be determined. Applying this principle, we determined the conduction band offset (CBO) and valence band offset (VBO) at the interface of CdS / SnS-based compounds doped with Ba atoms.

[0083] Figure 10 shows the VBM of Ba-doped SnS compound (Ba-dope Tin Sulfide: BTS). EF (BTS) and CBM EF (BTS), and VBM of CdS compounds EF (CdS) and CBM EF The analysis results for (CdS) are shown below. From this result, the band gap energy (E g ) is 1.57 eV {|CBM EF (BTS) |+|VBM EFConsidering that the band gap of SnS compounds is 1.3 to 1.4 eV, this value also indicates that the band gap is expanded by about 200 meV by doping Ba atoms into SnS compounds. The CBO and VBO at the CdS / BTS interface were found to be -0.41 and +1.38 eV, respectively. Previous research on SnS compounds has revealed that the CBO at the CdS / SnS interface is -0.4 to -0.5 eV, which is almost equal to the CBO of CdS / BTS determined in this experiment. Therefore, it was revealed that the reason why the band gap of BTS is wider than that of SnS compounds is that the upper edge of the valence band is lowered by doping with Ba atoms.

[0084] FIG. 11 shows the electron affinity and ionization potential of a CdS compound and a SnS compound doped with Ba atoms (denoted as BTS in the figure) when the electron affinity of the CdS compound is assumed to be 4.1 eV. It can be concluded that the lowering of the valence band edge (VBM) (i.e., the smaller valence band offset) suppresses the generation of p-type carriers regardless of the position of the Fermi level, making it easier to make the film of an SnS-based compound doped with Ba atoms n-type. From the above results, it is possible to determine whether SnS compounds contain Sn atoms such as Ba atoms. 2+ It has been found that a SnS-based compound semiconductor composition doped with a divalent cation atom having an ionic radius larger than the ionic radius of CdS can reduce the band offset at the interface between CdS and SnS even when the SnS-based compound semiconductor composition is heterojunctioned with an n-type CdS compound semiconductor composition.

[0085] In addition, from the results of Examples 1-1 to 1-3 using the above-mentioned manufacturing method 1, it was found that the SnS compound having a rectangular crystal structure composed of Sn atoms and S atoms and one or more kinds of atoms doped in the SnS compound were included, and at least one of the doped atoms was Sn. 2+The compound semiconductor composition thin film is formed by mixing a metal target containing Sn and a metal target containing Sn. 2+ A metal target containing an atom that will become a divalent cation having an ionic radius larger than that of Sn is prepared, and both metal targets are irradiated with Ar ions while supplying H2S gas, or Sn and Sn 2+ It was found that this can be produced by preparing a target containing a mixture of atoms that will become divalent cations with an ionic radius larger than that of Ar and HS gas, and irradiating the target with Ar ions while supplying HS gas.

[0086] Next, a thin film of a compound semiconductor composition was formed, the compound semiconductor composition including a SnS compound having a rectangular crystal structure composed of Sn and S atoms, and one kind of atoms doped in the SnS compound, at least one of the doped atoms being Ca atoms, and further including Cl atoms selected from halogen atoms as the atoms doped in the SnS compound. This film formation method is shown in the following manufacturing method 2.

[0087] <Manufacturing method 2> A thin film was formed in the same manner as in the above-mentioned manufacturing method 1, except that three types of targets were used: a target made of Sn metal, a target made of Ca metal, and a target made of Sn metal and SnCl2 powder pressed and solidified. SnCl2 powder was used as the source of Cl atoms to be doped.

[0088] (Example 2-1) According to the above-mentioned manufacturing method 2, a thin film of a compound semiconductor composition was formed by doping the SnS compound having a rectangular crystal structure with Ca atoms and Cl atoms at various concentrations. For comparison, a thin film of a compound semiconductor composition was also formed (film formation temperature: 270°C and 320°C) in which the SnS compound was doped with Cl atoms at various concentrations without doping with Ca atoms. Then, the amount of Cl atoms taken up (i.e., the content) in each compound semiconductor composition of the formed thin film was investigated. The results are shown in FIG. 12. The doping concentration of Ca atoms refers to the Ca atom content (i.e., doping amount) in the compound semiconductor composition formed into a thin film, and is expressed in atomic % (at%) relative to the compound semiconductor composition, the Cl atom concentration from the target refers to the Cl atom content atomic % (at%) in the target composed of Sn metal and SnCl2 powder pressed and solidified, and is expressed in atomic % (at%) relative to the target composition, and the Cl atom concentration in the thin film refers to the Cl atom content (i.e., doping amount) in the compound semiconductor composition, which is the formed thin film, and is expressed in atomic % (at%) relative to the compound semiconductor composition. Therefore, the Cl atom content in the compound semiconductor composition formed into a thin film means the doped Cl atom concentration, and corresponds to the vertical axis of FIG. 12. The horizontal axis of FIG. 12 corresponds to the Cl atom content in the target composed of Sn metal and SnCl2 powder pressed and solidified. In FIG. 12, the diamonds represent compound semiconductor compositions in which a SnS compound having a rectangular crystal structure, which is formed at a film-forming temperature of 270° C., is doped with Cl atoms without doping with Ca atoms. In the figure, ▲ represents a compound semiconductor composition in which a SnS compound having a rectangular crystal structure, which was formed at a film-forming temperature of 320° C., was doped with Cl atoms without doping with Ca atoms. In the figure, the black circles represent compound semiconductor compositions in which a SnS compound having a rectangular crystal structure and a deposition temperature of 270°C is doped with Ca atoms at various concentrations (2.7 atomic %, 1.8 atomic %) and further doped with Cl atoms. In the figure, ■ represents a compound semiconductor composition in which a SnS compound having a rectangular crystal structure, formed at a film formation temperature of 320° C., is doped with 2.0 atomic % Ca atoms and further doped with Cl atoms.

[0089] Each concentration was quantified by EDX (energy dispersive X-ray analysis) (Horiba, Ltd. EX-220).

[0090] As shown in FIG. 12, the compound semiconductor composition in which an SnS compound having a rectangular crystal structure is doped with Cl atoms but not with Ca atoms and formed at a film formation temperature of 270° C. has a significantly smaller ratio of the concentration of Cl atoms doped in the thin film to the increase in the concentration of Cl atoms from the target, compared to a compound semiconductor composition in which the SnS compound is doped with Ca atoms and also doped with Cl atoms and formed at the same film formation temperature of 270° C. In fact, as shown in FIG. 12, in the compound semiconductor composition not doped with Ca atoms, when the Cl atom concentration from the target reaches 7 atomic %, the Cl atom concentration doped in the thin film finally exceeds the line showing the doping amount required for an n-type SnS-based compound semiconductor composition (i.e., the doping amount required for an n-type SnS-based compound semiconductor composition is achieved), and even if the Cl atom concentration from the target is then increased to 18 atomic %, the Cl atom concentration doped in the thin film remains at approximately 0.6 atomic %. On the other hand, in a compound semiconductor composition in which an SnS compound having an orthorhombic crystal structure and a film formation temperature of 270° C. is doped with Ca atoms at 2.7 atomic % and further doped with Cl atoms, when Cl atoms are doped from the target, the Cl atom concentration doped in the thin film immediately reaches the doping amount required for an n-type SnS compound semiconductor composition, and when the Cl atom concentration from the target reaches 7 atomic %, the Cl atom concentration doped in the thin film reaches 1 atomic %, which is nearly twice the value of the compound semiconductor composition not doped with Ca. Also, in a compound semiconductor composition in which an SnS compound having an orthorhombic crystal structure and a film formation temperature of 270° C. is doped with Ca at 1.8 atomic % and further doped with Cl atoms, when the Cl atom concentration from the target reaches 18 atomic %, the Cl atom concentration doped in the thin film rises to around 3 atomic %.

[0091] The above-mentioned tendency is the same even when the film formation temperature is set to 320°C. In fact, in a compound semiconductor composition in which a SnS compound having a rectangular crystal structure and formed at a film formation temperature of 320° C. is doped with Cl atoms without doping with Ca atoms, even if the Cl atom concentration from the target is increased to 30 atomic %, the Cl atom concentration doped in the thin film remains low at only about 0.7 atomic %. On the other hand, in a compound semiconductor composition in which a SnS compound having a rectangular crystal structure is doped with 2.0 atomic % Ca atoms and further doped with Cl atoms, and which is formed at the same film formation temperature of 320° C., the concentration of Cl atoms doped in the thin film significantly exceeds 2.5 atomic %, even when the concentration of Cl atoms from the target is 7 atomic %, which is far lower than 30 atomic %. Therefore, it was confirmed that the compound semiconductor composition in which a SnS compound having a rectangular crystal structure is doped with Ca atoms and further doped with Cl atoms has a significantly higher ratio of the Cl atom concentration doped in the thin film to the increase in the Cl atom concentration from the target, compared to a compound semiconductor composition in which the SnS compound is doped with Cl atoms but not with Ca atoms.

[0092] Although not shown in the figure, this tendency was similar even when Ca atoms were replaced with Ba atoms or Sr atoms.

[0093] Therefore, it was confirmed that an n-type SnS-based compound semiconductor composition can be obtained by doping an SnS compound having an orthorhombic crystal structure with Ca atoms, Sr atoms, or Ba atoms, and further doping the SnS compound with halogen atoms such as Cl atoms, and that the n-type SnS-based compound semiconductor composition significantly increases the amount of halogen atoms doped compared to an SnS-based compound semiconductor composition in which the SnS compound is doped with halogen atoms such as Cl atoms without being doped with Ca atoms, Sr atoms, or Ba atoms. 2+According to the SnS-based compound semiconductor composition doped with a divalent cation atom having an ionic radius larger than that of the SnS compound, the SnS compound further contains one or more atoms selected from halogen atoms such as Cl atoms, and an n-type SnS-based compound semiconductor composition can be provided. 2+ It has been found that the amount of halogen atoms incorporated into the SnS-based compound semiconductor composition can be significantly increased compared to a SnS-based compound semiconductor composition that is not doped with divalent cation atoms having an ionic radius larger than that of the SnS-based compound semiconductor composition.

[0094] (Example 2-2) Next, according to the above-mentioned manufacturing method 2, a thin film of a compound semiconductor composition was formed by doping Cl atoms without doping Ca atoms to an SnS compound having a rectangular crystal structure, and a thin film of a compound semiconductor composition was formed by doping Ca atoms at a concentration of 2.0 atomic % to the SnS compound and further doping Cl atoms. The definition of the concentration was the same as in Example 2-1, and the Cl atom concentration doped in the former was 0.6 atomic % with respect to the compound semiconductor composition that was the thin film formed, and the Cl atom concentration doped in the latter was 2.7 atomic % with respect to the compound semiconductor composition that was the thin film formed. Both thin films were subjected to RTA (Rapid Thermal Annealing) treatment at 580°C for 10 seconds in an argon atmosphere. The equipment used for the RTA treatment was Mila-500 manufactured by Alpac Riko. The amount of chlorine contained in each film after the RTA treatment was quantified using EDX (Energy Dispersive X-ray Analysis) (Horiba EX-220 manufactured by Horiba).

[0095] As a result, in a thin film of a compound semiconductor composition in which a SnS compound having a rectangular crystal structure was doped with Cl atoms without doping with Ca atoms, the doped Cl atoms of 0.6 atomic % were reduced to below the detection limit.On the other hand, in a thin film of a compound semiconductor composition in which the SnS compound was doped with Ca atoms at a concentration of 2.0 atomic % and further doped with Cl atoms, the doped Cl atoms of 2.7 atomic % were reduced to 2.6 atomic %, with almost no change.

[0096] Although not shown in the figure, this tendency was similar even when Ca atoms were replaced with Ba atoms or Sr atoms.

[0097] Therefore, it was confirmed that the SnS-based compound semiconductor composition in which a SnS compound having a rectangular crystal structure is doped with Ca atoms and further doped with halogen atoms such as Cl atoms has stably fixed doped halogen atoms, compared with a SnS-based compound semiconductor composition in which the SnS compound is doped with halogen atoms such as Cl atoms without doping with Ca atoms. 2+ It has been found that by using an atom having a function of fixing the halogen atom (for example, any one or more of Ca, Sr, and Ba atoms) as an atom that becomes a divalent cation having an ionic radius larger than the ionic radius of the halogen atom, an n-type SnS-based compound semiconductor composition can be stably provided even under severe manufacturing conditions.

[0098] In addition, from the results of Examples 2-1 and 2-2 in which the manufacturing method 2 was used, it was found that the SnS compound, which is composed of Sn atoms and S atoms and has a rectangular crystal structure, and one or more kinds of atoms doped in the SnS compound are included, and at least one of the doped atoms is Sn. 2+The compound semiconductor composition further includes an atom doped in the SnS compound that is an atom that becomes a divalent cation having an ionic radius larger than that of the SnS compound, and the atom doped in the SnS compound includes one or more atoms selected from halogen atoms. 2+ A metal target containing an atom that will become a divalent cation having an ionic radius larger than that of the target is prepared, and both metal targets are irradiated with Ar ions while supplying H2S gas, or Sn or a tin halide and Sn 2+ It was found that this can be produced by preparing a target containing a mixture of atoms that will become divalent cations with an ionic radius larger than that of Ar and HS gas, and irradiating the target with Ar ions while supplying HS gas.

[0099] <Manufacturing method 3> We also tried to form a thin film of a compound semiconductor composition in which a SnS compound having a rectangular crystal structure is doped with Ca atoms and Cl atoms by another method. As described above, the doped Ca atoms, Sr atoms, or Ba atoms are Sn 2+ These are atoms that form divalent cations with an ionic radius larger than that of the cation of A thin film of the SnS-based compound semiconductor composition doped with 2.5 atomic % of Ca atoms, which was formed by Production Method 1, was heated to about 95°C on a hot plate, and SnCl4 liquid was dropped onto the film. This resulted in the formation of a thin film of the compound semiconductor composition in which the SnS compound having an orthorhombic crystal structure was doped with Ca atoms and Cl atoms.

[0100] (Example 3-1) For the compound semiconductor composition which was a thin film formed according to the above-mentioned manufacturing method 3, the Seebeck coefficient (unit: μV / K) by dropping an SnCl 4 solution was measured as follows. Using the temperature difference on the hot plate, where the temperature in the center is high and the temperature in the area off the center is low, one of the four corners of the thin film formed was placed in the center of the hot plate with indium attached as an electrode, and the other corner diagonally opposite the center was placed at the furthest position from the center on the hot plate with the same indium attached as an electrode. The temperature of the hot plate was set to 100°C, and the electromotive force difference between one corner of the thin film in the center of the hot plate (the hottest part was 95°C) and the diagonal corner (the coldest part was 75°C) was measured with a digital multimeter (KEYSIGHT 34461A) to examine the change in the Seebeck coefficient over time. The results are shown in Figure 13. As shown in FIG. 13, immediately after the SnCl4 solution was added, the Seebeck coefficient exhibited a negative value indicating that the composition was an n-type compound semiconductor. Over time, the negative value became larger and the n-type became stronger, and after about 500 seconds the Seebeck coefficient exhibited a constant value. Although not shown in the figure, this tendency was similar when no Ca atoms were doped, or when the Ca atoms were replaced with Ba atoms or Sr atoms.

[0101] Therefore, from the results of this experiment, it was confirmed that an SnS-based compound semiconductor composition in which an SnS compound having an orthorhombic crystal structure is doped with Ca atoms, Sr atoms, or Ba atoms and the SnS compound is further doped with halogen atoms such as Cl atoms becomes an n-type SnS-based compound semiconductor composition. 2+ It has been found that an n-type compound semiconductor composition can be provided by doping an SnS-based compound semiconductor composition with a divalent cation atom having an ionic radius larger than that of the n-type compound semiconductor composition, the SnS compound further containing one or more atoms selected from halogen atoms such as Cl atoms.

[0102] <Manufacturing method 4> A compact of a compound semiconductor composition in which a SnS compound having a rectangular crystal structure was doped with Ca atoms and Cl atoms was produced by the following method. Figure 14 shows the high-pressure synthesis apparatus used to manufacture the green compact and a conceptual diagram of the process. A powder mixture of Sn or SnCl2 powder and S powder was added with CaS, BaS, SrS, or two or more of these sulfides of Ca, Ba, or Sr atoms, so that the atomic ratio of the Ca, Ba, or Sr atoms contained in the sulfide to the Sn atoms contained in the Sn or SnCl2 powder was 1:1, and the mixture was filled into a capsule for high-pressure synthesis (specifically, a molybdenum capsule), and sintered under a high pressure of 25,000 atmospheres at 600°C for 12 hours. A green compact was produced as a sintered body produced in this way.

[0103] (Example 4-1) A compound semiconductor powder compact was produced by doping a SnS compound having a rectangular crystal structure with Ca atoms, Ba atoms, or Sr atoms and Cl atoms at concentrations of 1.0 atomic % and 2.0 atomic %, respectively, and the Seebeck coefficient of the produced powder compact was measured. As a result, the Seebeck coefficient values ​​(unit: μV / K) of all the compacts showed negative Seebeck coefficients, and it was confirmed that all were n-type. Specifically, the Seebeck coefficient value (unit: μV / K) when the doped Ca atomic concentration and Cl atomic concentration were 1.0 atomic % and 2.0 atomic %, respectively, was -1330, the Seebeck coefficient value (unit: μV / K) when the doped Ba atomic concentration and Cl atomic concentration were 1.0 atomic % and 2.0 atomic %, respectively, was -1240, and the Seebeck coefficient value (unit: μV / K) when the doped Sr atomic concentration and Cl atomic concentration were 1.0 atomic % and 2.0 atomic %, respectively, was -1225. Incidentally, the Seebeck coefficient value (unit: μV / K) of a compact of a compound semiconductor doped with 2.0 atomic % Cl atoms without doping with any of Ca atoms, Ba atoms, or Sr atoms was 2069, confirming that it was a p-type. Therefore, it was confirmed that an SnS-based compound semiconductor composition in which an SnS compound having an orthorhombic crystal structure is doped with Ca atoms, Sr atoms, or Ba atoms and the SnS compound is further doped with halogen atoms such as Cl atoms, becomes an n-type SnS-based compound semiconductor composition even if it is in the form of a compact. 2+ It has been found that an n-type compound semiconductor composition doped with a divalent cation atom having an ionic radius larger than that of the SnS compound, the SnS compound further containing one or more atoms selected from halogen atoms such as Cl atom, can be produced in the form of a compact.

[0104] In addition, from the results of Example 4-1 using the above-mentioned manufacturing method 4, it was found that the SnS compound having a rectangular crystal structure contains Sn atoms such as Ca atoms, Sr atoms, or Ba atoms. 2+ The SnS-based compound semiconductor composition is doped with a divalent cation atom having an ionic radius larger than that of the n-type compound semiconductor composition, and the SnS compound further contains one or more atoms selected from halogen atoms such as Cl atoms. 2+ A sulfide powder containing an atom that becomes a divalent cation with an ionic radius larger than that of Sn 2+ It was found that it can be produced by adding atoms that form divalent cations with an ionic radius larger than that of Sn atoms in an atomic ratio of 1:1 to Sn atoms, filling the mixture into a capsule for high-pressure synthesis, and sintering it at a high pressure of 20,000 atmospheres or more and a high temperature of 600°C or more.

[0105] <Manufacturing method 5> A thin film was formed in the same manner as in Manufacturing Method 2 described above, except that three types of targets were used: a target made of Sn metal, a target made of Ba metal, and a target made of Sn metal and SnBr2 powder pressed and solidified. SnBr2 powder was used as the source of Br atoms to be doped. The equipment used for this film formation and a conceptual diagram of the process are shown in Figure 15.

[0106] (Example 5-1) By the above-mentioned manufacturing method 5, a thin film of a compound semiconductor composition (specifically, an SnS-based compound semiconductor composition having an Sn concentration of 48 atomic %, an S concentration of 43 atomic %, a Ba concentration of 5 atomic %, and a Br concentration of 4 atomic %) was formed by doping the SnS compound having a rectangular crystal structure with Ba atoms and Br atoms. In this film formation, two types of thin films were formed, a thin film formed at a film formation temperature of 120°C and a thin film formed at a film formation temperature of 240°C. The Seebeck coefficient (unit: μV / K) of the SnS-based compound semiconductor composition thin film formed was measured using the same device as in Example 3-1, but the SnCl4 solution was not dropped. At this time, the temperature of the hot plate was set to 100°C, and the difference in electromotive force between one corner of the thin film at the center of the hot plate (the hottest part was 80°C) and the diagonal corner (the coldest part was 60°C) was measured with a digital multimeter (KEYSIGHT Corporation 34461A) to examine the Seebeck coefficient (unit: μV / K). For the thin film formed at a film deposition temperature of 120°C, the difference in electromotive force was -2720μV and the Seebeck coefficient was -136μV / K, and for the thin film formed at a film deposition temperature of 240°C, the difference in electromotive force was -2980μV and the Seebeck coefficient was -149μV / K. From these results, it was confirmed that both of the two types of SnS-based compound semiconductor compositions (i.e., compound semiconductor compositions in which the SnS compound having a rectangular crystal structure is doped with Ba atoms and Br atoms) produced were n-type compound semiconductor compositions.

[0107] <Manufacturing method 6> A target made of the above-mentioned Sn metal and H2S gas were used as the sources of Sn atoms and S atoms of the SnS compound, respectively, and a target made of Ca metal was used as the source of doped metal atoms, and a thin film was formed in the same manner as in the above-mentioned manufacturing method 1. (Example 6-1) By the above-mentioned manufacturing method 6, specifically, a thin film of a compound semiconductor composition (hereinafter also referred to as "Ca-atom-doped SnS-based compound semiconductor composition") was formed, which contains an SnS compound having a rectangular crystal structure composed of Sn atoms and S atoms and one type of atom doped in the SnS compound, the doped atom being a Ca atom. The doped Ca atom concentration was 2 atomic %. The Seebeck coefficient (unit: μV / K) of the formed thin film was measured using the same device and under the same conditions as in Example 3-1. For comparison, a thin film of an SnS compound semiconductor composition (hereinafter also referred to as "SnS compound semiconductor composition") consisting of two atoms, Sn atoms and S atoms, without doping with Ca atoms was also formed in the same manner as in the above-mentioned manufacturing method 1, except that a target serving as a supply source of the doped metal atoms was not used, and the Seebeck coefficient (unit: μV / K) of the formed thin film was measured using the same device and under the same conditions as in Example 3-1. The measurement results are shown in Figure 16. As shown in Figure 16, it was confirmed that the thin film of the SnS-based compound semiconductor composition doped with Ca atoms exhibited a much larger negative Seebeck coefficient than the thin film of the SnS compound semiconductor composition not doped with Ca atoms.

[0108] <Manufacturing method 7> A solar cell was manufactured using the thin film formed by the manufacturing method shown in the above manufacturing method 1 (i.e., thin films of three types of compound semiconductor compositions in which a SnS compound having an orthorhombic crystal structure is doped with Ca atoms, Sr atoms, or Ba atoms), and the output characteristics of the solar cell were examined. Hereinafter, for convenience, a thin film of a SnS-based compound semiconductor composition in which a SnS compound having an orthorhombic crystal structure is doped with Ca atoms will be referred to as a "Ca-SnS film", a thin film of a SnS-based compound semiconductor composition in which a SnS compound having an orthorhombic crystal structure is doped with Sr atoms will be referred to as a "Sr-SnS film", and a thin film of a SnS compound compound semiconductor composition in which a SnS compound having an orthorhombic crystal structure is doped with Ba atoms will be referred to as a "Ba-SnS film". A schematic diagram showing the configuration of the manufactured solar cell is shown in Figure 17. Specifically, the solar cell was manufactured as follows. First, an ITO (Indium Tin Oxide) film was formed as a lower electrode on a soda lime glass substrate (the substrate corresponds to the "SLG" part in FIG. 17) (the ITO film corresponds to the "ITO" part in FIG. 17), and a thin Ca-SnS film was formed thereon by the sputtering method described in Manufacturing Method 1 (the thin film corresponds to the "pA,E-SnS" part in FIG. 17). Then, a CdS (cadmium sulfide) film was formed on the thin film by the chemical bath deposition method. Specifically, a dispersion mixture of thiourea (NH2CSNH2), ammonia water, and cadmium sulfate hydrate (CdSO4·8 / 3H2O) was placed in a water bath at 80°C for 16 minutes to form a CdS (cadmium sulfide) film (the CdS film corresponds to the "CdS" part in FIG. 17). Furthermore, an AZO (aluminum doped zinc oxide) film was formed. Specifically, an AZO film was formed by depositing zinc oxide doped with 5 wt% aluminum to a thickness of 350 nm by a deposition method using a magnetron sputtering method using a transport device at 150°C (the AZO film corresponds to the "AZO" part in Figure 17). An aluminum electrode was placed on the top as an upper electrode (the aluminum electrode corresponds to the "Al" part in Figure 17). The Ca concentration of the Ca-SnS film was adjusted so that the band gap was 1.8 electron eV. Of course, the Ca concentration was in the range of 0.1 atomic % or more and less than 20 atomic %. The band gap of 1.8 electron eV was confirmed by optical measurement. Specifically, it was confirmed by Tauc plot obtained from absorption and reflection spectra using a SHIMAZU Solidspec-3700DUV spectrophotometer. In this way, a solar cell using a Ca-SnS film was manufactured. In addition, the solar cell using the Sr-SnS film and the solar cell using the Ba-SnS film were manufactured in the same manner as the solar cell using the Ca-SnS film described above, except that the thin Ca-SnS film was replaced with the Sr-SnS film or the Ba-SnS film. Therefore, the Sr concentration of the Sr-SnS film and the Ba concentration of the Ba-SnS film were also adjusted so that the band gap was 1.8 electron eV. Of course, the Sr concentration and the Ba concentration were within the range of 0.1 atomic % or more and less than 20 atomic %. In this manner, solar cells having the configuration shown in Fig. 17 were manufactured. Therefore, the three types of solar cells manufactured have a configuration in which an SnS-based compound semiconductor composition, in which an SnS compound having a rectangular crystal structure is doped with Ca atoms, Sr atoms, or Ba atoms, and a CdS compound semiconductor composition are heterojunctioned. (Example 7-1) In order to confirm whether the three types of solar cells manufactured by the above-mentioned manufacturing method 7 function as solar cells, the following measurements were carried out. The output characteristics of the three types of solar cells manufactured by the above-mentioned manufacturing method 7 were measured under conditions generally called standard test conditions (STC) (specifically, when the solar radiation intensity was 1.0 kW / m 2 The measurements were taken under standard test conditions, with the solar cell temperature at 25°C. As an example, the measurement results of the output characteristics of a solar cell using a Ba-SnS film (film thickness: 800 nm) as the thin film of the SnS-based compound semiconductor composition are shown in FIG. 18. FIG. 18 shows the output characteristics of the solar cell as the relationship between current density and voltage, i.e., JV characteristics. Here, the vertical axis represents the current density (unit: mA / cm 2 ), and the horizontal axis is voltage (unit: V). The intercept of the vertical axis is the short-circuit current density (Jsc), and the intercept of the horizontal axis is the open-circuit voltage (Voc). The short-circuit current is the maximum current that the solar cell can output, and the open-circuit voltage is the maximum voltage that the solar cell can output. The current density is calculated by multiplying the output current (mA) by the surface area (cm) of the thin film. 2) is calculated. The fill factor (FF) is defined by the point where the product of Jsc and Voc is the largest (i.e., the maximum output point), and the conversion efficiency of the solar cell is calculated as the product of Jsc, Voc, and FF divided by the solar radiation intensity. As shown in FIG. 18, it was confirmed that the Ba-SnS film in heterojunction with CdS exhibits diode characteristics (i.e., rectification). The area of ​​the gray zone in FIG. 18 indicates the conversion efficiency (%) of the solar cell using the Ba-SnS film as the thin film, and the value was calculated to be 0.22%, confirming that the solar cell can operate sufficiently. Although not shown in the figure, two types of solar cells with different film thicknesses were further manufactured by the same method as the above-mentioned manufacturing method 7 using Ba-SnS films with film thicknesses of 200 nm and 400 nm as the thin film. The output characteristics of each solar cell were measured by the same method as the output characteristics of the solar cell with a film thickness of 800 nm. It was confirmed that each thin film exhibited diode characteristics (i.e., rectification) like the Ba-SnS film, and that each solar cell using each thin film was fully operable as a solar cell based on the calculated conversion efficiency (%). In addition, the output characteristics of other solar cells manufactured by the above-mentioned manufacturing method 7 (specifically, a solar cell using a Ca-SnS film as the thin film of the SnS-based compound semiconductor composition and a solar cell using a Sr-SnS film as the thin film of the SnS-based compound semiconductor composition) were measured in the same manner as the output characteristics of the solar cell using the Ba-SnS film. However, the film thickness of each thin film was set to two types, 200 nm and 400 nm. It was confirmed that whichever thin film was used, the diode characteristics (i.e., rectification) were exhibited like the solar cell using the Ba-SnS film, and that the solar cells using any thin film were fully operable as solar cells based on the calculated solar cell conversion efficiency (%). In FIG. 19, the results of the conversion efficiency (%) of the solar cell measured in this embodiment are shown as the relationship between the thickness and the conversion efficiency (%) of the thin film (i.e., Ca-SnS film, Sr-SnS film, and Ba-SnS film) of the SnS-based compound semiconductor composition used in each solar cell. As shown in FIG. 19, a significant conversion efficiency (%) was observed for each solar cell, and it was confirmed that the solar cell operates sufficiently as a solar cell. From FIG. 19, it was confirmed that the solar cell using the Ba-SnS film having a thickness of 800 nm, in particular, exhibits the best output characteristics as a solar cell having a configuration in which an SnS-based compound semiconductor composition in which an SnS compound having a rectangular crystal structure is doped with Ca atoms, Sr atoms, or Ba atoms and a CdS compound semiconductor composition are heterojunctioned. [Industrial Applicability]

[0109] The present invention is expected to be useful for thermoelectric materials, which require high conversion efficiency, as well as for thin-film solar cells and multi-junction solar cells. In addition to solar cells, these materials can be used in a wide variety of industries where the development of semiconductors with high conversion efficiency is expected (e.g., the automotive, electrical and communications, aerospace, and military industries).

Claims

1. A compound semiconductor composition having an orthorhombic crystal structure in which a SnS compound is doped with one or more types of atoms, At least one of the doping atoms is Sn 2+ is an atom that becomes a divalent cation having an ionic radius larger than the ionic radius of The band gap of the compound semiconductor composition is larger than the band gap of the SnS compound before doping with the atoms. Compound semiconductor composition.

2. Sn 2+ 2. The composition according to claim 1, wherein the atom that becomes a divalent cation having an ionic radius larger than that of the compound represented by the formula (I) is one or more atoms selected from the group consisting of Ca atoms, Sr atoms, and Ba atoms.

3. Sn 2+ 3. The composition according to claim 1, wherein the content of atoms forming divalent cations having an ionic radius larger than that of the compound semiconductor composition is 0.1 atomic % or more and less than 20 atomic % based on the compound semiconductor composition.

4. The composition according to claim 1 or 2, wherein the crystal structure belongs to space group Pnma, which is space group 62 of the International Tables for Crystallography.

5. 3. The composition according to claim 1, wherein the atoms doped in the SnS compound include one or more atoms selected from halogen atoms.

6. The composition according to claim 1 or 2, wherein the atoms doped in the SnS compound include Cl atoms or Br atoms.

7. 6. The composition according to claim 5, wherein the content of halogen atoms is 0.25 atomic % or more and 25 atomic % or less based on the compound semiconductor composition.

8. The composition of claim 5 which is an n-type semiconductor composition.

9. A thin film comprising the composition of claim 1 or 2.

10. A thin-film solar cell comprising the composition of claim 1 or 2.

11. A top cell for a multi-junction solar cell comprising the composition of claim 1 or 2.

12. A middle cell for a multijunction solar cell, comprising the composition according to claim 1 or 2.

13. A multi-junction solar cell comprising the composition of claim 1 or 2.

14. 3. The composition of claim 1 or 2 in the form of a powder compact.

15. A thermoelectric material comprising the composition of claim 14.

16. (i) a metal target containing Sn or a tin halide; and 2+ A metal target containing an atom that will become a divalent cation having an ionic radius larger than that of H is prepared, and both of the metal targets are charged with H 2 By irradiating Ar ions while supplying S gas, or (ii) Sn or a tin halide and Sn 2+ A target is prepared by mixing an atom that becomes a divalent cation having an ionic radius larger than that of the target, and the target is mixed with an atom that becomes a divalent cation having an ionic radius larger than that of the target. 2 By irradiating Ar ions while supplying S gas, A method for producing the thin film of claim 9.

17. A mixture of Sn or tin halide powder and S powder is added to the mixture. 2+ A sulfide powder containing an atom that becomes a divalent cation having an ionic radius larger than that of Sn 2+ 15. A method for producing the composition according to claim 14, comprising adding an atom which becomes a divalent cation having an ionic radius larger than the ionic radius of Sn to Sn atoms in an atomic ratio of 1:1, filling the mixture into a capsule for high pressure synthesis, and sintering the mixture at a high pressure of 20,000 atmospheres or more and at a high temperature of 600°C or more.

Citation Information

Patent Citations

  • Production of sns semiconductor sintered film

    JP1994321538A

  • Solar battery

    JP2016054237A

  • N-TYPE SnS SEMICONDUCTOR AND SOLAR CELL USING THE SAME

    JP2019178012A